Powered instruments for managing Thornwaldt’s cyst: our experience - Sathe, Nilam U.; Ahmed, Saad; Rani, Diksha; Ingle, Amar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Thornwaldt’s cyst (TC) is a benign, midline cystic swelling located in the roof of nasopharynx. Produced by persistent notochord remnants, it is relatively rare. There is no sex predilection. Most cases are diagnosed during the second and third decade. Nasal endoscopy is the best to visualise the disease and in case of doubt, imaging is helpful. Most of the cysts are asymptomatic but when the cyst is large or causing symptoms, surgery is the treatment of choice. A 32-year-old male, presented with bilateral decreased hearing since 2 and half years, with no other ear symptoms. Audiogram showed bilateral conductive hearing loss, with impedance audiogram showing bilateral type B curve. CT scan of Paranasal sinuses and nasopharynx was suggestive of midline cystic mass arising from roof of nasopharynx. Patient was taken up for nasal endoscopic surgery using microdebrider. A 17-year-old male, presented with complaints of nasal obstruction with no otologic symptoms like aural fullness, decreased hearing. MRI showed oval lesion attached to roof of nasopharynx. Patient was planned for surgery using coblation. TC although considered benign and often asymptomatic but it may be overlooked due to its overlapping of symptoms with other conditions. This under recognition highlights the need for increased awareness and high quality imaging in the diagnosis. While surgical intervention remains the mainstay of treatment for symptomatic cysts but minimally invasive technique like endoscopic drainage reduces recovery time and complication rate. Powered instruments use in managing cysts, resulting in minimal morbidity and improved postoperative outcomes.